The Legal Position of Amicus Curiae's Opinion on Criminal Judicial Processes in Indonesia - Krisnalita, Louisa Yesami; Mutiarany, Mutiarany; Sharon, Grace; Mohamad, Ani Munirah (JUSTITIA JURNAL HUKUM, 2022)
Amicus curiae comes from the Latin "amicus" which means "friend" and "curiae" which means "court". In English it is called "Friends Of Court" in Indonesian it is called Friends of Court. Amicus curiae is derived from Roman law, which was later developed and practiced in the common law system, which allows courts to invite third parties to provide information or legal facts relating to unfamiliar issues. Amicus curiae's opinion, when displayed in court, can increase the judge's confidence in the criminal evidence system. Regarding the Amicus curiae's opinion, there is no regulation in the provisions of the criminal procedural law so that the judge is still hesitant to use the Amicus curiae's opinion. The research method used is normative juridical. The results of the research in writing that because Amicus curiae does not yet have clear rules in the judiciary in Indonesia, it is difficult for judges to consider the opinion of Amicus curiae submitted in court and also difficult to relate to the evidence contained in Article 184 of the Criminal Procedure Code because The Amicus curiae does not yet have a clear form in the Indonesian judiciary